1977
DOI: 10.1152/jappl.1977.43.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, respiration, skin and body temperature during cold water immersion

Abstract: Subjects who had not been exercising, were immersed for 20 min in water at 13 degrees C after ingestion of alcohol. During the immersion period, total ventilation, end-tidal PCO2, rectal temperature, aural temperature, and mean skin temperature were recorded. Control experiments were carried out at the same water temperature. Blood samples (3 ml), taken immediately before the immersion period, were analyzed by gas liquid chromatography. The mean blood alcohol level was 90+/-11.2 mg-(100 ml)-1. There was no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

1979
1979
1997
1997

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…On the basis of the evidence obtained during the present experiment, and that from relevant earlier studies (Martin et al 1977;Keatinge and Evans 1960), it is concluded that in young, healthy individuals who know what is going to happen to them, moderate concentrations of alcohol in the blood (18-28 mmol 7 1 -1 , 85-130 mg 7 100 ml -1 ) may slightly reduce the initial responses to immersion in cold water. The practical significance of these reductions is questionable.…”
Section: Discussionsupporting
confidence: 68%
“…On the basis of the evidence obtained during the present experiment, and that from relevant earlier studies (Martin et al 1977;Keatinge and Evans 1960), it is concluded that in young, healthy individuals who know what is going to happen to them, moderate concentrations of alcohol in the blood (18-28 mmol 7 1 -1 , 85-130 mg 7 100 ml -1 ) may slightly reduce the initial responses to immersion in cold water. The practical significance of these reductions is questionable.…”
Section: Discussionsupporting
confidence: 68%
“…Experiments in man show that a moderate dose of alcohol can reduce body temperature in a dry, cold environment (Graham and Dalton 1980;Graham 1981), but not in cold water (Martin et al 1977;Kuehn et al 1978;Fox et al 1979). Fox et al (1979) have suggested that the absence of an alcohol effect on skin temperature in cold water is due to the very intense stimulation by the water on the receptors, which causes strong vasoconstriction and thereby reduces heat loss due to alcohol, and this is reflected in the unchanged core temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Since earlier experiments have shown that alcohol in moderate amounts does not significantly alter cold-tolerance during immersion in cold water (Martin et al 1977;Kuehn et al 1978;Fox et al 1979), it was decided to study the effect of a moderate dose of alcohol on the activity of the skeletal muscle in anesthetized rabbits immersed in ice-cold water. This was done by monitoring the adenine nucleotides and the phosphorylation state of the adenylate system (ATP/ADP × Pi) after alcohol infusion and cold immersion; the phosphorylation state being an important ratio for the regulation of the respiration rate (Klingenberg 1961;Owen and Wilson 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Whether such consumption accelerates the rate of progress into hypothermia of a victim in cold water has not been fully resolved. Martin et al ( 1977) showed no effect of alcohol (blood concentration of 90 ing% ) on body temperature and ventilation responses during the initial 20 min of immersion in 13°C watcr. However, studies on immersion hypothernlia (Hayward et al 1975a(Hayward et al , 1975b, have shown that factors which influence core cooling rate into hypothermia begin to show their effect only after about the first 15 min of immersion.…”
mentioning
confidence: 89%